PENGEMBANGAN SISTEM INFORMASI PROFIL PERUSAHAAN UNTUK LAYANAN PELANGGAN BERBASIS WEB MENGGUNAKAN METODE AGILE - Nurhakim, Mizan; Tedi Budiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Advancing technology requires the government to provide better services to the public. Therefore, a web-based system was created at Perumda Tirta Intan Garut. This system is used to showcase the company's profile and also to serve the customers. This system was developed using Agile methodology. The tools used are CodeIgniter 4 and MySQL. The main features of this system are providing information about the company, business development, and also offering services to customers. The services that customers can use are registration, viewing bills, checking prices, inquiries, and reporting issues. There is also a menu for admins and a page about data and figures. System testing was conducted using Black Box Testing. The result is that all parts can function according to the user's wishes. With this system, information and services for customers can be provided more easily, clearly, and transparently. Now, customers can receive better, more accurate, and faster services from the company.